2021
DOI: 10.1016/s2468-2667(21)00102-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial, temporal, and demographic patterns in prevalence of smoking tobacco use and initiation among young people in 204 countries and territories, 1990–2019

Abstract: Background Ending the global tobacco epidemic is a defining challenge in global health. Timely and comprehensive estimates of the prevalence of smoking tobacco use and attributable disease burden are needed to guide tobacco control efforts nationally and globally. MethodsWe estimated the prevalence of smoking tobacco use and attributable disease burden for 204 countries and territories, by age and sex, from 1990 to 2019 as part of the Global Burden of Diseases, Injuries, and Risk Factors Study. We modelled mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(162 citation statements)
references
References 55 publications
4
113
0
9
Order By: Relevance
“…This situation may indicate that smoking is more likely to cause HAdV infections in high-altitude areas. Previous studies showed that a greater proportion of smoking in high-altitude areas may be partly attributed to social aspects of low education attainment, poverty, and lack of health insurance coverage ( Mercado et al., 2021 ; Reitsma et al., 2021 ). In the chest CT scans, the main manifestations were patchy shadow and bilateral ground-glass shadow.…”
Section: Discussionmentioning
confidence: 99%
“…This situation may indicate that smoking is more likely to cause HAdV infections in high-altitude areas. Previous studies showed that a greater proportion of smoking in high-altitude areas may be partly attributed to social aspects of low education attainment, poverty, and lack of health insurance coverage ( Mercado et al., 2021 ; Reitsma et al., 2021 ). In the chest CT scans, the main manifestations were patchy shadow and bilateral ground-glass shadow.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is much more work needed ahead. Over 1 billion people worldwide still use tobacco products, 2 and the tobacco industry continues to aggressively fight the enactment and effective implementation of proven policy interventions. 3 The demand and supply measures outlined in the FCTC, adopted by the World Health Assembly in 2003, are considered a floor (after all, the Framework Convention was based on the best evidence available through the dawn of the 21st century).…”
Section: Global Tobacco Use and Policy Interventionsmentioning
confidence: 99%
“…In 2019, there were an estimated 155 million smokers aged between 15 and 24 years -equivalent to 20.1% of young men and 5.0% of young women, globally. Two-thirds (65.5%) of all current smokers began smoking by age 20, and 89% of smokers began by age 25, highlighting a critical age window during which individuals develop nicotine addiction and transition to become established smokers [14][15][16].…”
Section: Prevalence Of Smoking and Youth Vapingmentioning
confidence: 99%
“…Turkey, Jordan, and Zambia had the largest increases in number of young female smokers. Over half of countries, worldwide, showed no progress in reducing smoking among 15-24 years old [14][15][16].…”
Section: Prevalence Of Smoking and Youth Vapingmentioning
confidence: 99%
See 1 more Smart Citation